Retraction: (Etika Bisnis Islam Pedagang Sapi dan Dampaknya terhadap Kesejahteraan Pedagang di Kecamatan Masbagik Kabupaten Lombok Timur) - Ahmad Hulaimi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2017)
This study aims to analyze the application of Islamic business ethics among cattle traders and its impact on their welfare in Masbagik District, East Lombok Regency. The research method used a qualitative approach with data collection techniques through in-depth interviews, observations, and document studies. The results showed that the implementation of Islamic business ethics principles, such as honesty, justice and social responsibility, had a significant effect on improving the economic and social welfare of the traders. However, there are also some obstacles in its implementation, such as the lack of in-depth understanding of sharia and market pressure. This study provides recommendations for businesses and policy makers to strengthen Islamic financial literacy and encourage ethical business practices to improve people's welfare.